The Effect of Learning on Heart Rate and Behavior of European Starlings (Sturnus vulgaris) - Glassman, L.W. (J Exp Zool A Ecol Integr Physiol, 2019)
Wild-caught European starlings (Sturnus vulgaris) were exposed to a learning task in order to determine whether heart rate (HR) and behavior responses to the learning activated the sympathetic nervous system. Birds learned to discriminate between images of opposite convexity (concave and convex) based on shading cues in a closed economy (food only available through task completion). Once learned, the task was changed in three ways: (1) manipulating the angle and shape of the image; (2) altering the availability of the task; and (3) reversing the positive stimulus. HR, used as an index of catecholamine release, was measured during each change to determine whether having to alter previously established behaviors in order to learn new behaviors elicited a sympathetic response. Starlings decreased their HR during the initial discrimination training and did not alter their HR when presented with modified images or when the positive stimulus was reversed. However, HR increased when the task became unavailable and decreased upon its return, suggesting that preventing task performance was perceived as stressful. Birds also modified their behavior when tasks were changed. The number of trials/min decreased during the reversal treatment, as did the success rate, suggesting that starlings may try to conserve energy when access to food diminishes. This is also supported by the decrease in perch hops/min when the task was unavailable and the subsequent increase upon its return. Overall, these results suggest that learning per se does not activate the sympathetic nervous system and therefore is not a stressor for wild birds.